The Role of The Principal for Educational Reform in Indonesia - Firman Mansir; Halim Purnomo; Masyhar Sa’adi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
This article described the role of a principal as a leader and manager in educational institutions in responding and contributing to educational reform in Indonesia. The leadership of the principal is one of the important points to advancing Indonesia. Along with their roles, principals should be able to bear the burden of responsibility in preparing the quality of education by the tasks and goals to be achieved. The research method in this article used a literature study with a qualitative approach. The results showed that there are many roles that a school principal can contribute to educational reform, such as improving educational facilities and infrastructure for students. Thus, the improvement of good facilities will support the learning and reflect the manifestation of the seriousness of a leader and manager in educational institutions.